The current approach to determine wound age and vitality - Pakiş, Işıl (The Bulletin of Legal Medicine, 2016)
Research on vitality and wound age estimation are the classic fields in forensic medicine. Vitality as one of the basic issues in forensic practice deals with the question, whether injuries were caused during lifetime of an individual. It plays a role in connection with traumatic deaths due to sharp and blunt force injuries, burns or drowning. In relation to the vitality of wounds it must be asserted that an injury of the body was caused during lifetime. In spite of large literature data there is still considerable demand of further research and practical transfer of knowledge and techniques to daily casework. The study aims to classify current methods and materials used in evaluation of wound age and viability and determine their practical application in forensic medicine.